Romance cinema for debunking gender bias of non-egalitarian couple relationships in higher education - Morales-Romo, Beatriz; Hernández-Serrano, María J.; Morales-Romo, Noelia (Frontiers in Education, 2023)
Romance cinema may recreate cisgender heterosexual couple representations by means of image-making, with the use of gender bias or traditional images that have considerable effects on how women and men are represented or are expected to behave, which may confront egalitarian models of relationships. This study aims to analyze how the traditional model of couples is represented in the 20 romantic highest-grossing movies selected from the years 2000-2010, and whether the reading of non-egalitarian images awakens different meanings and reflections by experts and undergraduates in Higher Education (areas of education and communication). For this aim, a mixed methodology was used, first qualitative (six in-depth interviews with academics and film analyses of the selected movies), then quantitative (questionnaire to 251 undergraduates analyzing films), and then qualitative again (personal reports from the same students). Results confirmed the reflective making of gender bias and non-egalitarian images of couple relationships in six of the box-office films, with moderate percentages in categories of Submission, Dominance, Dependence, and higher percentages of Manipulation, either for/from women or men. The study concludes that romance cinema was positively valued by students and academics as an enabling cultural product for the analysis, reflection, and deconstruction of non-egalitarian images, so that higher education students can be guided to critically seek suitable understandings of gender and couple relationships.